Risk Burden of Heat-Related Morbidity Due to Urban Heat Island Effect in Tamalanrea District, Makassar - Khairunnisa, Angelia; Ihsan, Ihsan; Patandianan, Marly (Media Kesehatan Masyarakat Indonesia, 2023)
One of the problems in the urban environment is the rise in land surface temperature and heat buildup (Urban Heat Island) around built-up areas. People living in UHI areas will experience an increased risk of health burdens. Therefore, early identification for disaster mitigation is needed to achieve a sustainable city. This study aims to provide an overview of the risk of the spread of heat-related diseases based on the relative risk value in Tamalanrea District. This study considers the relationship between Land Surface Temperature (LST) values in 2019, 2020, and 2021 with the incidence of heat-related diseases obtained from the Integrated Health Center Recording and Reporting System (IHCRRS) in Tamalanrea District, Makassar City in 2019, 2020 and 2021. Data analysis used Pearson correlation test and Standardized Morbidity Ratio (SMR) epidemiological approach. The results showed a significant relationship between LST values and the incidence of hypertension, heart disease, and asthma in 2019 and the incidence of headache and hypertension in 2021. Bira and Kapasa sub-districts were at the highest risk for the spread of heat-related diseases than other sub-districts with a risk score > 4.00 (very high). These findings can be used to help guide public health interventions and preventive urban planning efforts.